1993
DOI: 10.1111/j.1468-2885.1993.tb00077.x
|View full text |Cite
|
Sign up to set email alerts
|

The Three Paradigms of Mass Media Research In Mainstream Communication Journals

Abstract: Scholars who write about the paradigms influencing mass media research differ in their speculations. This study was conducted to provide an empirical analysis by examining six characteristics of mass media research articles published in eight major communication journals. The social science paradigm was found to account for over 60% of the studies, while the interpretive paradigm accounted for about 34% and the critical paradigm less than 6%. It was concluded that the social science paradigm, while being the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 8 publications
1
21
0
4
Order By: Relevance
“…60.8% of all studies have study designs with no theoretical reasoning, rationale or discussion at all (table 4). Similarly, Potter, Cooper and Dupagne (1993) found that 91.9% of their analysed articles had no theoretical foundations. A study by Potter and Riddle (2007) found the same result for 57.1%.…”
Section: Theoretical Orientationsmentioning
confidence: 98%
“…60.8% of all studies have study designs with no theoretical reasoning, rationale or discussion at all (table 4). Similarly, Potter, Cooper and Dupagne (1993) found that 91.9% of their analysed articles had no theoretical foundations. A study by Potter and Riddle (2007) found the same result for 57.1%.…”
Section: Theoretical Orientationsmentioning
confidence: 98%
“…Additionally, research effort at the institute should be built (Potter et al, 1993). The last two are mentioned to broaden the scope of research so as to not only include attention to legal, historical and ideologically inspired policy studies, but also to focus on message encoding and signification through semiological and other 'framing ', 'bracketing', and 'formatting' strategies (McLeod et al, 1994) ?…”
Section: • Research Agenda For the Research Prong Of The Institutementioning
confidence: 99%
“…As is traditional in some survey research, Potter et al (1993Potter et al ( , 1995 and Abelman (1996) appear to be thinking in terms of univariate population estimates, that is, descriptive (Farber, 1952) or particularistic (Kruglanski, 1975) research. In this scenario, the principle focus is usually an attempt to make estimates of univariate values from a sampled population.…”
Section: Literature Reviewmentioning
confidence: 99%